Ultra-Thin Rechargeable Lithium Ion Batteries on Flexible Polymer: Design, Low Temperature Fabrication and Characterization. Issue 9 (1st January 2017) - Oukassi, Sami; Giroud-Garampon, Cédric; Poncet, Séverine; Salot, Raphaël
Abstract : In this work we developed flexible rechargeable thin film lithium ion batteries based on all-solid-state materials. The flexible batteries were fabricated using low temperature sequential physical vapor deposition techniques. A thin film battery (TFB) architecture consisting of Ti/V2 O5 /LiPON/Li/encapsulation multilayer was deposited on flexible polyimide substrate. To the best of our knowledge, the obtained TFBs are among the thinnest reported with an overall thickness of 50 μm including substrate, active layers and encapsulation stack. The fabricated TFBs delivered discharge capacity as high as 0.15 mAh (1.5 cm² of cathode area) upon galvanostatic cycling at 30 μA.cm −2 within 3.8–1.5 V voltage range. The capacity decreased during cycling with an average fading rate of 0.25% over 100 cycles. Electrochemical impedance spectroscopy (PEIS) measurements and modeling analysis revealed an increase of the internal resistance during cycling. Furthermore, it was shown that the internal resistance increase was induced by a progressive decrease of the electrolyte/electrodes contact area. TFBs having the same architecture and cell design were fabricated on two substrates: a flexible polyimide foil and a rigid silicon wafer. Electrochemical characterization showed a clear influence of substrate type on TFBs discharge capacity and internal resistance variations during cycling, the results are discussed within this paper